Speech Etiquette as a Means of Intercultural Communication (On the Example of the French and Uzbek Languages) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article highlights the national and cultural features of speech labels in French and Uzbek languages.